Model Kurikulum Pendidikan Pra Nikah Untuk Membentuk Keluarga Sakinah: Studi Implementasi Surat Edaran Dirjen Bimas Islam tentang Kursus Calon Penganten di Kantor Urusan Agama Kabupaten Karawang - Munir Huda; Didin Hafidhuddin; Ulil Amri Syafri; Irfan Syauqy Beik (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2016)
Marriage is one of the implementation of the command of Allah SWT and sunnah of the prophet Muhammad SAW. however, very few people know about it. Therefore the Miniastry of Religious Affairs of the Indonesian Republic through the District‘s Offie of Religious, Affairs had been providing courses to bride and bridegroom candidates by giving knowledges understandings and skills of the family life/household. The focus of the study is directed to the two main issues: Firstly, discussing the impelementation of Circular letter of the General Director of Islamic Community Guidance about Bridal Candidate Courses in the Offic of Religious Affairs throughout Karawang. Secondly, discussing the of course’s Curriculum Model of Muslim Candidate bride-bridegroom. The conclusion is that the implementation of the course’s curriculum of the bride and bridegroom candidate in Religious Affairs Office Karawang wasn’t implemented yet systematically. This is due to the lack of a model or guidance that can be used as a reference in its implementation . Therefore, to response these problems, researcher offered Curriculum Model of Muslim Bridal Candidate Course based sakinah family for all KUA troughout Karawang district. Through the offer of curriculum model is expected to be a reference or guideline in conducting pre-marital education in the Office of Religious Affairs troughout Karawang.